The prevalence of probable sarcopenia and intrinsic capacity impairment among a group of community-dwelling older people in an urban area in Cameroon - Marie-Josiane Ntsama Essomba; Régine Mylène Mballa Mba; Jean Jacques Noubiap; Florence Denise Mvondo Lema; Nadine Simo; Maturin Tabue Teguo (PLoS ONE, 2026)
Although intrinsic capacity serves as an indirect measure of an individual’s functional reserve, whether and in which way it interacts with sarcopenia is still to be addressed in Cameroon. This study aimed to describe the relationship between probable sarcopenia and domains of intrinsic capacity among older people in Cameroon. This cross-sectional study included community-dwelling older aged ≥ 60 years from two senior citizen’s association in Cameroon. Probable sarcopenia was assessed using grip strength and Short Physical Performance Battery (SPPB). Screening for intrinsic capacity(IC) impairment was done using the Integrated Care to Older People(ICOPE) approach. Probable sarcopenia was defined by low handgrip strength and low physical performance. We included variables with a p -value < .1 in the multivariable analysis model. The significance level was P < .05. We included 108 participants [64.8% female, mean age (standard deviation) 70.4 (6.6) years]. The prevalence of probable sarcopenia was 34.3%. All participants had a positive screening for IC impairment and the main impaired domains were vision (88%), locomotion (61.1%) and cognition (50%). The probable sarcopenia group was likely to be older (72.9 ± 7.9 vs 69.6 ± 6.1 P = .018), achieved lower education ( P = .012) and had frequent history of stroke ( P = .038). After adjusting for age, sex and comorbidities, participants with impaired vitality (OR3.60, 95%CI1.08–11.94) were likely to have probable sarcopenia. Participants with preserved locomotion (OR 0.12, 95%CI 0.02–0.66) and a lower number of IC domains impaired (OR 0.52, 95%CI 0.29–0.95) were less likely to have probable sarcopenia. With regard to the components of sarcopenia, preserved locomotion (OR 0.01, 95%IC 0.012–0.07) was associated with a higher physical performance. Lower number of IC domains impaired was associated with higher physical performance (OR 0.29, 95%CI0.12–0.76) and higher handgrip strength (OR0.58, 95%CI 0.37–0.92).This study suggest that IC impairment is associated to probable sarcopenia in this group of older adults in Cameroon. Further research on IC trajectories monitoring and incident confirmed sarcopenia as outcome are needed to plan targeted interventions taking into account local resources.